Impact of COVID-19 pandemics upon pulmonary hypertension patients: insights from BNP-PL national database. (14th October 2021) - Mamzer, A; Kasprzak, J D; Waligora, M; Kurzyna, M; Mroczek, E; Mularek-Kubzdela, T; Pruszczyk, P; Gasior, M; Lewicka, E; Karasek, D; Kusmierczyk-Droszcz, B; Mizia-Stec, K; et al.
Abstract: Introduction: COVID-19 pandemic has caused not only an increase in overall and cardiovascular mortality, but also hindered access to health care, diagnosis and treatment of diseases other than coronavirus infection. Aim: Assessment of the impact of the SARS-CoV-2 pandemic on the rate of diagnosis and therapy of pulmonary hypertension (PH) in Poland, along with an analysis of the incidence and course of COVID-19 among patients (pts) diagnosed with PH, treated under the National Health Fund program, registered in the national BNP-PL database. Methods: The records of the complete population of Polish pts treated under the National Drug Program of PH (PAH and CTEPH), registered in the national database of BNP-PL, updated on an ongoing basis by all PH centers, were analyzed. The frequency of SARS-CoV-2 infections, the clinical severity of their course and the mortality were reviewed, taking into account the specific therapies used. The basic clinical characteristics of the group of sick and deceased patients were compared to the remaining patients registered in the BNP-PL database. The rate of increase of new diagnoses ended with inclusion in the Drug Program between March and December 2020, compared to the corresponding periods of the previous year, and the change in the treatment profile were compared. Results: The analysis included 1704 pts (PAH 1134, CTEPH 570). The incidence of SARS-CoV-2 infections was 3.8% (n=65), including PAH 2.7% (n=46) and CTEPH 3, 2% (n=18). 32 patients (49%) required hospitalization. Mortality rate was 28% (18/65) – including 7/18 outside of hospital. Those who died due to COVID-19 were older (mean age 68.4±15.8 vs. 50.8±18.8 yrs; p<0, 001), had higher WHO class and more cardiovascular comorbidities (4±2, 06 vs. 2, 66±1, 8; p=0, 01) (Table 1). During the pandemic the number of new diagnoses of PH markedly decreased compared to the corresponding period in 2019 (total 150 vs. 203, PAH 90 vs. 123, CTEPH 60 vs. 80, respectively). A significant increase in total mortality was also observed in the PH group (9, 72 vs. 5, 85%). Moreover, escalation of specific PH therapy decreased significantly (14, 7% vs. 21, 6%). Incidence of COVID-19 study group was lower than estimated for general Polish adult population (3, 8% vs. 6, 5%). Conclusions: COVID-19 pandemic deeply influenced the diagnostic and therapeutic process of pulmonary hypertension by reducing the number of new diagnoses, escalation therapy and increased overall mortality in this population. This may be due in part to the conversion of some PAH centers into hospitals treating patients infected with SARS-CoV-2, as well as to patients' fear of admitting to hospital despite clinical deterioration. Pulmonary hypertension is linked to markedly increased mortality in COVID-19, similarly for PAH and CTEPH. Intriguing finding of lower infection rate may be linked to protective lifestyle or specific therapies. FUNDunding Acknowledgement: Type of funding sources: None.